KONTRIBUSI KOMUNIKASI INTERPERSONAL DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL MEDIATOR PADA PT. MAJU SEJAHTERA LESTARI - Elvie Maria; Kristanty M. N. Nadapdap (Universitas Methodist Indonesia, 2021)
The purpose of this research is to analyze the contribution of interpersonal communication, organizational climate on employees’ performance through work motivations. The population in this study were all employees totaling 118 people. Sampling techniques using the Slovin formula and obtained as many as 91 employees. Variable this research consisting interpersonal communication, organizational climate, work motivation, employees’ performance. Data collection methods used were questionnaires. Analysis of the data used is multiple linear regression analysis and path analysis using SPSS 24. The results of the study states that contribution variable interpersonal communication, organizational climate, work motivation to explain employees performance variables is 57. 3 %. The results of research indirect effect on employees’ performance through work motivation showed organizational climate are not supported, but interpersonal communication supported. The results showed also that work motivation is a partial mediating variables on the influence of interpersonal communication and organizational climate on employee performance. This research is expected to be beneficial for PT. MSL improve employees’ performance.